1908
DOI: 10.1037/13065-000
|View full text |Cite
|
Sign up to set email alerts
|

A study of the influence of custom on the moral judgment.

Abstract: There are no known copyright restrictions in the United States on the use of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1915
1915
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The tyro will realize that by questioning the answer will generally be obtained that stealing and assault and so on are pernicious deeds, as considered in the abstract, and wUl also realize that the answer gives no criterion of what the subject's judgment wUl be in the face of opportunity or provocation.Ĥ owever, the powers of general moral judgment and particularly of the comprehension of moral issues involved in a given situation, are sometimes important to appreciate. F. C. Sharp (110) has done interesting work with non-offenders on this subject of moral discrimination, and we have utilized, in modification, in our Test XXI, some of his methods. A short narration involving some points of ethical judgment is orally presented, and a discriminating response is called for.…”
Section: B Methods Of Giving Mental Testsmentioning
confidence: 99%
“…The tyro will realize that by questioning the answer will generally be obtained that stealing and assault and so on are pernicious deeds, as considered in the abstract, and wUl also realize that the answer gives no criterion of what the subject's judgment wUl be in the face of opportunity or provocation.Ĥ owever, the powers of general moral judgment and particularly of the comprehension of moral issues involved in a given situation, are sometimes important to appreciate. F. C. Sharp (110) has done interesting work with non-offenders on this subject of moral discrimination, and we have utilized, in modification, in our Test XXI, some of his methods. A short narration involving some points of ethical judgment is orally presented, and a discriminating response is called for.…”
Section: B Methods Of Giving Mental Testsmentioning
confidence: 99%
“…Sie sind ähnlich stimulierend wie die Ausführungen über Kausalität, Gerechtigkeit und Konsistenz. Geht man nun noch einen weiteren Schritt zurück in der historischen Betrachtung, so kann man auf eine Arbeit stoßen, die mehr als hundert Jahre zurück moralische Urteilsprozesse empirisch untersucht hat (Sharp, 1897/98) und als Vorbild für zukünftige empirische Forschung dienen kann in Verbindung mit den Erörterungen bei einer Nachfolgeuntersuchung von Sharp (1908) und den Ausführungen bei Heider (1958). Diese Arbeiten weisen auf den Einfluß der Normen und der Kultur auf die ethische Haltung hin, in Ergänzung zu den kognitiven Entwicklungsstufen verbunden mit dem Lebensalter in der Entwicklungspsychologie.…”
Section: Einführungunclassified
“…until he desires to see certain rules, however few and bare in context, obeyed by man as such" (Sharp, 1908a, p. 266). Sharp (1908b) still continued to search for the best method of studying moral judgments. He reaffirmed his early statement about studying morality: "The question whether moral judgments are the product of custom and kindred forces is at once one of fundamental importance for theory and practice, and one that can never be decided by an appeal to introspection" (p. 6).…”
Section: Early Studies Of Moralitymentioning
confidence: 99%
“…From this, he concluded that general social rules function by providing a stabilizing effect on moral judgments. Sharp (1908b) noted that there were six major reasons why people would observe these general rules: (a) concern about the effect of their example on others, (b) concern about creating a habit of breaking rules, (c) concern about losing the confidence of others, (d) concern about losing confidence in others, (e) fear of others acting in the same way, and (f) concern about not knowing where one rule ends and another begins.…”
Section: Early Studies Of Moralitymentioning
confidence: 99%
See 1 more Smart Citation